Effect of Soybean Digital Farmer Field School on Knowledge Levels of Respondents in Maharashtra. - Kadam, Kaustubh; Ahire, Milind; Dhadwad, Manohar; Dahatonde, Anjali (Indian Journal of Extension Education, 2025)
The study was conducted in 2023-2024 to assess the knowledge level of participant and non-participant farmers regarding Standard Operating Procedures (SOPs) for soybean cultivation in Ahilyanagar district, Maharashtra. An ex-post-facto research design was used, covering 150 soybean growers (75 participants and 75 non-participants) selected from fifteen villages across three talukas through multistage sampling and were assessed on their knowledge level of Standard Operating Procedures (SOPs)for soybean cultivation. Results showed that 76% of participants had high knowledge versus 6.67% of non-participants. Significant differences across nine key soybean cultivation aspects were confirmed by Z-tests. Higher knowledge among participants may be attributed to live expert-led sessions and collaborative group learning, fostering practical skills and experience sharing. Regression analysis identified education, scientific orientation, and techno-savviness as key predictors, while traditional socio-economic factors were less influential in participants' knowledge score on SOPs for soybean cultivation. The study highlights DFFS’s potential to overcome traditional barriers, empowering farmers through enhancement in their knowledge about SOPs for soybean cultivation, ultimately promoting sustainable soybean cultivation and improved productivity.